Re-imagining marketing as societing: A critical appraisal of marketing in a developing country context. Issue 3 (20th March 2018) - Kashif, Muhammad; Fernando, P.M.P.; Altaf, Umair; Walsh, John
Abstract : Purpose: Marketing theory and practice is under severe criticism – socialists and the practitioners criticize marketing in its current form which calls for active efforts by marketers to reposition the discipline – making it beneficial to the masses. The Western world is thoroughly investigated based on the opinions of public regarding marketing as a discipline. However, studies which present a non-Western consumer's attitudes toward the role of marketing in a society are scant. This purpose of this study is to encapsulate Pakistani consumers' understandings and attitudes toward marketing with an emphasis on their perceptions of the ethicality and transformative power of the discipline. Design/methodology/approach: A purposive convenience sample of 40 professionals with diverse non-marketing backgrounds and of the widest possible demographic profile participated in in-depth, unstructured interviews. The content analysis and grounded theory method were used for the analysis. Findings: Marketing is appreciated for creating product awareness and, occasionally, combating social problems, but this positive image is clouded by severely criticizing it for promoting materialism, being irritatingly pervasive and pushy, as well as for using unethical and unfair practices. Practical implications: The study offers a valuable insight into the discipline's performative and social legitimation in a fast-growing Asian economy. The authors recommend paths for a positive repositioning of the discipline that will improve its public image and enhance its potential for being recognized as a force for positive social change. Originality/value: Further to enhancing our understanding of consumer attitudes toward marketing, this paper's value lies in it being the first ever exploration of the developing country perspective. Most importantly, it contributes to a debate that could enlighten the much-needed repositioning of marketing as a discipline to make it useful for masses.